Late Diagnosis of Systemic Scleroderma with Vascular Events: Clinical Case - Julia S. Bogomolova; Galina V. Santalova (Вопросы современной педиатрии)
Background. Timely diagnosis of systemic scleroderma (SS) can reduce the risk of complications and disability in patients. However, correct diagnosis is complicated by the diversity of disease clinical forms and variants. Clinical case description. SS in a boy under 5 years old was considered as congenital skin hemiatrophy, thus he was observed by dermatologist (treatment without effect). Methotrexate and prednisolone therapy was administered at the age of 5 years after diagnosing the SS. Subungual ulcers and distal phalanges osteolysis appeared and further progressed at the age of 10 years. In this regard the child was treated for onychomycosis outpatiently, however with no effect. Later the child was hospitalized. Vasotropic therapy (pentoxifylline, nifedipine, alprostadil) was carried out for 21 days with positive effect: decrease in the area and depth of subungual ulcers. Conclusion. Late diagnosis of SS has led to vascular events whereas incorrect interpretation of clinical signs led to their progression. Vasotropic therapy has achieved positive effect.